2018
DOI: 10.1089/jmf.2017.4026
|View full text |Cite
|
Sign up to set email alerts
|

The Red AlgaGracilariopsis chordaand Its Active Constituent Arachidonic Acid Promote Spine Dynamics via Dendritic Filopodia and Potentiate Functional Synaptic Plasticity in Hippocampal Neurons

Abstract: Exogenous neurotrophins can induce neuronal differentiation, outgrowth, survival, and synaptic function in the central nervous system. In primary cultures of rat hippocampal neurons, an ethanol extract of the red alga Gracilariopsis chorda (GCE) and its active compound arachidonic acid (AA) significantly increased the densities of dendritic filopodia and spines, promoted the expression of presynaptic vesicle protein 2 (SV2) and postsynaptic density protein 95 (PSD-95), induced robust synaptogenesis, and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Fucoxanthin has shown to exhibit neurite outgrowth activity (15.7–31% of cells to develop neurite outgrowth) at much lower concentrations (0.1–2 μM), in the absence of NGF support, indicating that this marine carotenoid could a potential neurotrophic molecule [ 136 ]. Gracilariopsis chorda and its active compound arachidonic acid modulated spine dynamics, and potentiated functional synaptic plasticity of hippocampal neurons [ 150 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
See 2 more Smart Citations
“…Fucoxanthin has shown to exhibit neurite outgrowth activity (15.7–31% of cells to develop neurite outgrowth) at much lower concentrations (0.1–2 μM), in the absence of NGF support, indicating that this marine carotenoid could a potential neurotrophic molecule [ 136 ]. Gracilariopsis chorda and its active compound arachidonic acid modulated spine dynamics, and potentiated functional synaptic plasticity of hippocampal neurons [ 150 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
“…Porphyra yezoensis and its compound taurine facilitated neuronal development and maturation of primary hippocampal neurons [ 152 ]. Gelidium amansii [ 153 , 154 , 155 , 156 ], Sargassum fulvellum [ 157 ], Undaria pinnatifida and Saccharina japonica [ 158 ], Gracilariopsis chorda [ 150 , 159 ], and carrageenophyte Kappaphycus alvarezii [ 160 , 161 , 162 , 163 ] promoted neuronal morphology and functions. Of these, G. amansii that exhibited neuromodulatory potentials in several studies [ 153 , 154 , 155 , 156 ] could be the most promising candidate for further isolation of neurotrophic agents and thus expects special attention of natural product chemists.…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acid is an important nutritional component that provides promising health benefits [39]. The study revealed a higher amount of omega-3 fatty acids, particularly DHA and EPA, found in hot smoked HDPS products, which are known to be effective in mitigating the onset of neurodegenerative complications in central nervous system neurons, cardiovascular disease progression, and arthritis [40][41][42]. PAHs are generally formed from incomplete combustion of organic matter such as wood materials while smoking and considered to be potential health hazards, in which BaP represents an effective genotoxic and carcinogenic to humans [43].…”
Section: Discussionmentioning
confidence: 99%
“…Fucoxanthin has shown to exhibit neurite outgrowth activity (15.7-31% of cells to develop neurite outgrowth) at much lower concentrations (0.1-2 μM), in the absence of NGF support, indicating that this marine carotenoid could a potential neurotrophic molecule [107]. Gracilariopsis chorda and its active compound arachidonic acid modulated spine dynamics, and potentiated functional synaptic plasticity of hippocampal neurons [140].…”
Section: Neurotrophic Activitymentioning
confidence: 99%